Cu- and Fe-codoped Ni porous networks as an active electrocatalyst for hydrogen evolution in alkaline medium - Hegde, Chidanand (2020)
Highly active catalysts from the earth-abundant metals are essential to materialize the low-cost production of hydrogen through water splitting. Herein, nickel porous networks codoped with Cu and Fe prepared by thermal reduction of presynthesized Cu, Fe-codoped Ni(OH)2 nanowires are reported. The sample consists of nanoparticles of ∼80 nm, which form highly porous network clusters of ∼1 μm with a pore size of 10–100 nm. Among the various doped compositions, the NiCu0.05Fe0.025 porous network exhibits the best catalytic activity with a low overpotential of 60 mV for a hydrogen evolution reaction (HER) in 1 M KOH solution and a specific activity of 0.1 mA cm–2 at 117 mV overpotential calculated based on the electrochemical active surface area (ECSA). The density functional theory calculations reveal that codoping of Fe and Cu into the Ni lattice results in a shift of d-bands of nickel to lower energy levels and thus in the reduced hydrogen adsorption energy (ΔGH = −0.131 eV), which is close to ΔGH for Pt (−0.09 eV). When NiCu0.05Fe0.025(OH)2 nanowires is used as an oxygen evolution reaction (OER) catalyst and is coupled with NiCu0.05Fe0.025 porous networks for overall water splitting, the NiCu0.05Fe0.025∥NiCu0.05Fe0.025(OH)2 catalyst couple achieves a current density of 10 mA cm–2 at 1.491 V, similar to that of the Pt/C∥RuO2 couple and offers a negligible loss in the performance when operated at 20 mA cm–2 for 30 h.